198k views
1 vote
I really need the answer to this please

I really need the answer to this please-example-1

1 Answer

4 votes

Answer:

y - 4 = (-3/2)(x + 3)^2

Explanation:

The vertex of the given graph is at (-3, 4), and the graph also goes through (-1, -2). Using the vertex equation of a parabola, y - k = a(x - h)^2, and inserting the given info: vertex at (-3, 4) => h = -3, k = 4; other point at (-1, -2) => x = -1, y = -2.

Then:

y - k = a(x - h)^2 becomes -2 - 4 = a(-1 + 3)^2, or:

-6 = 4a. Therefore, a = -6/4, or a = -3/2. The equation of this quadratic is:

y - 4 = (-3/2)(x + 3)^2

User Tomasz Gawel
by
6.0k points